IMPLEMENTASI TEKNOLOGI BLOCKCHAIN DALAM BIDANG AKUNTANSI DAN SUPPLY CHAIN MANAGEMENT : STUDI LITERATUR - Aulia, Dena (Department of Accounting-Faculty of Economic and Business (FEB), 2023)
This paper provides a literature review on recent research concerning blockchain-based accounting and supply chain management, with a particular focus on Indonesia as a developing country where blockchain technology is gaining prominence for scholarly investigation. The study examines the characteristics and architecture configurations of blockchain to ascertain suitable implementation approaches in various domains, including accounting, auditing, the public sector, and, notably, supply chain management. Furthermore, endogenous risks in supply chain management are identified to glean insights for future supply chain implementations. Additionally, a case study analysis is presented, drawing on a manufacturing industry supply chain management scenario to offer a deeper understanding of blockchain technology's implementation. Through this research, it is expected that awareness and understanding of the potential of blockchain technology in optimizing accounting and supply chain management in Indonesia can be enhanced.